2021
DOI: 10.1002/pssa.202100398
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Mechanical and Tribological Properties of Thin Al2O3 Coatings Fabricated by Atomic Layer Deposition and Radio Frequency Sputtering

Abstract: Thin Al2O3 films (150 nm thick) are deposited by atomic layer deposition (ALD) and radio frequency sputtering on Si substrates and submitted to annealing in N2 atmosphere at 900 °C for 90 min. X‐ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microscopy and energy dispersive X‐ray spectroscopy (SEM–EDS), nanohardness, and fretting wear measurements are used to infer the structural, morphological, mechanical, and wear properties of the as‐deposited and annealed films. Results show a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The 2‐layer TFE had a similar roughness as the ZnO film, as the surface roughness of the underlying ZnO layer is not mitigated by the AlO x layer on top of it, because the amorphous AlO x is very smooth and conformal to the topography of the underlying substrate, consistent with previous reports that showed that ALD and AP–SALD/AP–SCVD Al 2 O 3 can conformally coat complex structures. [ 25,38,39 ] The RMS roughness was reduced considerably for the 5‐layer TFE, approaching that of the single‐layer AlO x film. The smoothing effect of the multiple AlO x layers is attributed to the AlO x thin films interrupting the ZnO crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…The 2‐layer TFE had a similar roughness as the ZnO film, as the surface roughness of the underlying ZnO layer is not mitigated by the AlO x layer on top of it, because the amorphous AlO x is very smooth and conformal to the topography of the underlying substrate, consistent with previous reports that showed that ALD and AP–SALD/AP–SCVD Al 2 O 3 can conformally coat complex structures. [ 25,38,39 ] The RMS roughness was reduced considerably for the 5‐layer TFE, approaching that of the single‐layer AlO x film. The smoothing effect of the multiple AlO x layers is attributed to the AlO x thin films interrupting the ZnO crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…For aluminum powders specifically, the oxidized and hydrated surface layers can influence the powder packing, increase agglomeration, and be detrimental to the mechanical properties of fabricated parts. Recent work on alumina coatings has included characterization, including X-ray diffraction (XRD), atomic force microscopy (AFM), and energy dispersive spectroscopy (EDS) [13]. We hope to fill an important knowledge gap to help researchers identify the initial state, dehydration, and decomposition properties of aluminum powders in wide variety of states using a simplistic IR setup.…”
Section: Introductionmentioning
confidence: 99%
“…Coating deposition (solution a). Preliminary tests underscored the challenge of applying coatings thicker than a few microns using the available Radio Frequency (RF) Sputtering technology [20]. • The use of a flexible tape (solution b).…”
mentioning
confidence: 99%